Microwave-Assisted pyrolysis of waste plastics: A comprehensive review on process parameters, catalysts, and future prospects - K. M. Oajedul Islam; Nabeel Ahmad; Aniz Chennampilly Ummer; Usama Ahmed; Mohammad Nahid Siddiqui; Marcos Millan; Abdul Gani Abdul Jameel (Results in Engineering)
The ever-growing consumption of plastic products has led to significant environmental concerns due to their persistent nature and inefficient disposal practices. Thermochemical recycling, particularly pyrolysis, has emerged as a promising method to convert plastic waste into fuels and value-added chemicals. Among pyrolysis techniques, microwave-assisted pyrolysis (MAP) has gained considerable attention for its rapid heating, energy efficiency, and enhanced product yields. This review presents a comprehensive overview of the MAP of plastic waste, covering fundamental aspects such as feedstock preparation, selection of microwave absorbents and catalysts, and critical operating parameters. The impact of temperature, microwave power, catalyst type, and feedstock properties on the yield and quality of pyrolytic products, including bio-oil, syngas, and char—is thoroughly analyzed. Product characterization data and case studies from recent literature are synthesized in tabular and graphical formats. Special emphasis is placed on co-feeding strategies, hydrogen production, and the influence of catalyst structure on aromatic yield. Key challenges—such as hot spot formation, catalyst deactivation, and scale-up limitations—are identified. Finally, potential future directions are proposed, including the development of multi-stage MAP systems, integration with gasification processes, and pathways for industrial-scale deployment.